Free, Prior, and Informed Decision-Making About Proposed Development on Indigenous Territories in Northern Ontario - Arseneau, Courtney (Scholars Commons @ Laurier, 2019)
This case study examined the experiences of consultation and consent-seeking processes among nine Indigenous communities in northern Ontario that, individually and collectively, are faced with complex decisions to be made since the discovery of several significant mineral deposits on their traditional territories. In examining the processes involved in making informed development decisions, this dissertation addressed four key research questions: 1) What are the roles, processes, laws and rights frameworks that influence resource governance in the Matawa First Nations region? 2) How is free, prior, and informed decision-making described by people living and working in the Matawa First Nations region? 3) What are the needs, opportunities, and challenges in making informed decisions about proposed development? and 4) What role does community-level dialogue play in making informed decisions? This research included two community kitchen table talks where participants gathered to discuss their views on self-determined development, to share their experiences with proposed regional developments, and to dialogue about a vision for their community. Drawing from two table talks, five key informant interviews, and an analysis of key documents from the tribal council (2010-2018), several themes emerged to advance our understanding of free, prior, and informed decision-making about lands and resources. Key findings suggest that, while development decisions are highly technical, free, prior, and informed consent (FPIC) is fundamentally about the communities’ agency and their ability to meaningfully participate, to pursue their own meanings of prosperity, and to do so within the context of genuine partnerships with external government and industry proponents. Figures 3.1, 4.1, and 4.3 are presented to describe the complex organizational and interpersonal relationships associated with development decisions in the Matawa region. Lessons learned and considerations for future research are identified and discussed.